2020
DOI: 10.1177/1073274820945975
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Options for Advanced Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC), one of the most common lethal diseases in the world, has a 5-year survival rate of only 7%. Hepatocellular carcinoma has no symptoms in the early stage but obvious symptoms in the late stage, leading to delayed diagnosis and reduced treatment efficacy. In recent years, as the scope of HCC research has increased in depth, the clinical development and application of molecular targeted drugs and immunotherapy drugs have brought new breakthroughs in HCC treatment. Targeted therapy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…In recent years, molecular targeted therapy, such as lenvatinib, atezolizumab and bevacizumab, has emerged as a new cancer treatment method [ 32 ]. However, these treatment agents, except for sorafenib, were not reimbursed by Taiwan National Health Insurance (NHI) during the study period (2016–2019).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, molecular targeted therapy, such as lenvatinib, atezolizumab and bevacizumab, has emerged as a new cancer treatment method [ 32 ]. However, these treatment agents, except for sorafenib, were not reimbursed by Taiwan National Health Insurance (NHI) during the study period (2016–2019).…”
Section: Discussionmentioning
confidence: 99%
“…Kinase inhibitors other than sorafenib, like Lenvatinib, cabozantinib, and regorafenib, showed some good results, but none were superior to sorafenib. 29 As HCC is known to be a highly vascular tumor, drugs that act as vascular endothelium growth factor inhibitors with different mechanisms have been investigated as bevacizumab and Ramucirumab. Multiple drug categories have been investigated like a-Fetoprotein Targeted Drugs, and Glypican-3 Targeted Drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple drug categories have been investigated like a-Fetoprotein Targeted Drugs, and Glypican-3 Targeted Drugs. 29 The liver is a central immunomodulator that keeps the balance between protection and immunotolerance. 30,31 Deregulation of the liver immunological network is a hallmark of chronic liver disease and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] UHRF1 is a ubiquitin E3 ligase and contains at least 4 domains including a plant homeodomain domain, a ubiquitin-like domain, a RING domain, and a SET and RING associated (SRA) domain. [44][45][46][47] It was confirmed that UHRF1 could co-locate with DNA methyltransferase protein DNMT1 in the S phase. 48 The SRA domain of UHRF1 strongly binds to the physiological substrate for DNMT1.…”
Section: Introductionmentioning
confidence: 88%